An International Law Perspective on the Protection of Human Rights in the TRIPS Agreement an Interpretation of the TRIPS Agreement in Relation to the Right to Health. - Xiong, Ping (International studies in human rights., 2012)
This book analyses the relationship between the TRIPS Agreement and the right to health and relevant human rights norms by using the tools of treaty interpretation of public international law.